Brand Audit and Improvement Brand Artika - Agatari, Juwita; Desiana, Krisnati (The Indonesian Journal of Business Administration, 2015)
Abstract; the raising of modern people awareness toward healthcare in all aspect including sexual healthcare made the condom industry into a promising industry. PT. Mitra Rajawali Banjaran is the only one Indonesia local condom producer. With its Brand Artika which stands for Arti Kasih Sayang PT. MRB at first selling its product to fulfill government market through National Family Planning Coordinating Board (BKKBN). But on other side Artika Condom only grab 1% market share in commercial market nevertheless this brand is already produced and distributed in Indonesia for almost 30 years. Turned out that Artika faced business issue poor brand in the consumer mind and its awareness that PT. MRB believe that is the cause of it low purchasing by consumer in commercial market. To solve the business issue faced by this brand first is by analyzing internal and external factor from the company and especially from the brand Artika itself. In searching and solving the problem the brand audit method will be the tool for examines the health of the brand PT. MRB knows which problems that need to be fixed the most to entering commercial market. Either needs new brand or just simply improving the Artika brand. And the brand Audit in conjunction with market survey resulting that Artika is rarely know by consumer, having no special distinctive compared with other brand, having weak marketing program, poor packaging appearance, confusing association of brand name, known as worthless product and have poor distributing channel. And this kind of situation will need company to have new brand that more suitable for commercial marketÂ Keyword: marketing, brand audit, , brand improvement, condom industry